1998
DOI: 10.1016/s0885-3924(98)00067-0
|View full text |Cite
|
Sign up to set email alerts
|

End-of-Life Decisions and Advance Directives in Palliative Care

Abstract: In order to explore possible differences in the scope of end-of-life decisions and attitudes toward advance directives (AD) in palliative care, we conducted a survey of 159 patients in palliative care institutions and 93 health-care professionals experienced in palliative care in the United States, Germany, and Japan. Giving an AD in this clinical setting was considered important by patients and professionals. The prevalence of a formal written AD was 79% in the United States, 18% in Germany, and 9% in Japan. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(28 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…ADs was a well-covered theme. Studies explored awareness of ADs, use and compliance [138], [144], [145], [146], [147], [148], [149], [150], [151], [152] and desired level of bindingness [150], [153], [154], [155].…”
Section: Resultsmentioning
confidence: 99%
“…ADs was a well-covered theme. Studies explored awareness of ADs, use and compliance [138], [144], [145], [146], [147], [148], [149], [150], [151], [152] and desired level of bindingness [150], [153], [154], [155].…”
Section: Resultsmentioning
confidence: 99%
“…Participants were from one geographic location in northern California, limiting the generalizability of our results (50). Furthermore, approximately half of the participants contacted study staff in response to flyers, potentially resulting in selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, it is frowned upon when an individual takes unilateral decisions on issues of dying. The decisions on end of life care are preferably deferred to family members or community elders [9]. In Kenya, for example, 68.2% of respondents in one study indicated they would like a relative to be involved in end of life decision making [10].…”
Section: Introductionmentioning
confidence: 99%